The Effect of Problem-Based Learning Model Assisted by Contextual Videos on Students’ Learning Outcomes in The Subject of Sound Waves - Perwithasari, Ni Made Nitha; Sutrio; Harjono, Ahmad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This study aims to determine the effect of problem-based learning models assisted by contextual videos on student learning outcomes in sound wave material. The type of research used is a quasi-experimental design with nonequivalent control group design. The population in this study were all students of class XI MIA SMAN 4 Mataram. Sampling used a purposive sampling technique, so that XI MIA 3 students were obtained as a control group using a conventional learning model and XI MIA 4 as an experimental group using a problem-based learning model assisted by contextual video. The instrument used is an observation sheet for affective and psychomotor assessment, a multiple choice test that refers to the cognitive abilities of students from C1 to C6 as many as 18 items taking into account the validity, reliability, discriminatory power and difficulty level of the questions. Study result data were analyzed using parametric statistics, namely t-test polled variance with a significant level of 5% and obtained t_count of 3.77 and t_table of 1.99. According to the hypothesis testing criteria, if t_count>t_table, then Ho is rejected and Ha is accepted, so it can be concluded that the contextual video-assisted problem-based learning model influences student learning outcomes in sound wave material.